THE IMPLEMENTATION OF JIGSAW METHOD IN TEACHING SIMPLE PRESENT TENSE - Anisa Solihat; Trisnendri Syahrizal (IKIP Siliwangi, 2020)
This research used descriptive qualitative. The writer used tenth-grade Hotel Accomodation’s students of SMK Dwi Putra Sindangkerta as a subject research. In the process of English enrolling, the writer found out the problem on the subject in grammar, especially simple present tense. This skill is a structure that often used in daily conversation. But the students has more difficulties in enrolling simple present tense while it is very important to enroll because it can help them when they meet the foreign guest in the hotel later. We teach simple present tense easier using any method. One of them is the jigsaw method. This method often used more teacher in Indonesia because of this method easy to implement it. Thus, the writer researches the student to teach simple present tense to implement jigsaw method in other to understand easier by them. The writer applies jigsaw in some steps; they are pre-activity, divided into groups, the group leader selection, group reviewion activity, submitted an assignment, and evaluation. Teaching simple present tense used jigsaw can make a enrolling effectively, and it is improving students motivation to enroll simple present tense. Keywords: AKP’s Students, Simple Present Tense, Jigsaw Method